Salvage of distal non-target coil embolization with stent placement and intravenous eptifibatide in a ruptured, unsecured, atypical aneurysm. (27th March 2013) - Janjua, Nazli; Bulic, Sebina; Tan, Benedict C; Panichpisal, Kessarin; Miller, John
Abstract : Introduction: Small aneurysms may be challenging to embolize. In cases of subarachnoid hemorrhage (SAH) where treatment is delayed, physicians may have to balance the risks of certain required therapies (antiplatelet agents) with the risk of rerupture. We describe a case of a technically challenging anterior cerebral artery aneurysm requiring eptifibatide infusion prior to definitive aneurysm treatment. Case report: A 57-year-old woman with SAH, underwent coil embolization of a small fenestrated A1–A2 junction aneurysm. The procedure was complicated by downstream coil migration which was then treated with Enterprise stent placement in the pericallosal artery. This required subsequent infusion of a glycoprotein IIb/IIIa inhibitor until the aneurysm could be repaired surgically. Conclusions: Revascularization with a stent in a distal cerebral vessel may salvage inadvertent coil migration. Although it is undesirable to administer antiplatelet agents to patients with SAH, in these circumstances short acting agents may be used.